Evaluating Cognitive Load of a Laundry Service Worker: A Subjective Workload Assessment Technique Approach - Wulandari, Chandrawati Putri; Vincent, Adriel Maruli; Hassani, Gilang Fadly; Sunar, Muhammad Akbar; Aldhama, Shofa Aulia; Mufidah, Ilma (Journal of Advanced Technology and Multidiscipline, 2025)
Laundry service workers perform repetitive and physically demanding tasks, often under time constraints, leading to increased cognitive load. Cognitive load assessment is crucial for understanding workload distribution and optimizing task allocation in labor-intensive industries. This study evaluates the cognitive load of laundry service workers using the Subjective Workload Assessment Technique (SWAT). The analysis focuses on two primary phases: scale development and event scoring. The scale development phase involved rating three workload dimensions: time pressure, mental effort, and stress level. The event scoring phase analyzed workload variations across tasks and workers. The findings indicate that ironing is the most cognitively demanding task, followed by washing and moving to the dryer, while storing and customer retrieval generally impose lower workloads. Notably, differences in workload perception among workers highlight the need for task redistribution, process optimization, and potential ergonomic interventions. This study provides valuable insights into improving worker efficiency and well-being in service industries.